Correlation between Serum Ferritin and Heart Function in Children with Major Thalassemia at Dr. Soetomo Hospital - Evisina Hanafiati Frans; Mahrus A Rahman; Teddy Ontoseno; I Dewa Gede Ugrasena; R Fatchul Wahabe (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Background: Cardiac hemosiderosis in major thalassemia has a high mortality rate. Serum ferritin levels are routinely performed to measure body iron deposit Early detection of cardiac dysfunction by routine echocardiography is very important to prevent complications due to hemosiderosis. Objective: To analyze correlation between serum ferritin levels and heart function in thalassemia major children. Methods: A cross-sectional study involving children of thalassemia major less than 18 years in the pediatric hematology oncology outpatient clinic at Dr. Soetomo Hospital. The subjects were children diagnosed with thalassemia major who had received more than 10 transfusions and had ferritin levels above 500 µg / L. All subjects were taken through consecutive sampling and performed echocardiography to measure right ventricular systolic function, left ventricular systolic function, and diastolic function. The factors analyzed included serum ferritin levels, TAPSE index, ejection fraction, and E / A ratio. Statistical analysis using chi square. Results: A total of 82 children were taken as the study sample that met the inclusion and exclusion criteria, 1 sample was dropped out due to pneumonia. Serum ferritin was not correlated to right ventricular systolic function (Cramer's phi constant 0.14, p = 0.209). Serum ferritin was not correlated with left heart systolic function (Cramer's phi constant 0.187, p = 0.09). Serum ferritin was not related to diastolic function (Cramer's phi constant 0.124, p = 0.264). Conclusion: Serum ferritin level in major thalassemia was not correlated with cardiac function